Diálogos e interdições na formação inicial do professor: análise semiótica de relatos em torno das práticas - Rosa, Tânia Maria de Oliveira (2020)
The present thesis is the result of research carried out on the initial training of language teachers in an undergraduate degree in Language Arts. This case study aimed to analyze rationalized internship practices in the voice of the teacher in initial training to identify their perceptions about training and teaching performance in the learning process, inserted in two training spaces - the university and the field school. For this purpose, we chose as the subject reports of the experiences of students graduating from the Federal University of Tocantins between 2016 and 2018. We considered as corpus 1. twelve testimonials generated from semistructured interviews; 2. notes made in a field diary produced by observing the practice in the Supervised Internship subject of a university professor; 3. testimonials from Basic Education professionals associated to the State Education Secretariat of Tocantins, in the city of Araguaína (SEDUC-TO). As a theory of narrative analysis, we gathered discursive semiotics, using the categories of narrative syntax, considering the relationships operated under the regime of manipulation that implied transformations in the narrative path. Discursive semantics refers to it considering themes and figures that build an image of the school and the teacher training in the discourse of the interns. Based on the reviews brought by socio semiotics regarding narrativity, we dedicated chapters of analysis from the perspective of interaction regimes, issues related to the semiotics of space, in addition to the modalizations and passionate effects arising from the relationships between subjects and objects and between subjects/objects and practices, signaling, finally, a semiotic of the experienced. In this direction, we mobilized semiotics considering the levels of the relevance of a theory that describes the data and offers a way of analysis of teaching practices. Although teacher training is procedural and takes place during professional life, complexified in everyday experience, and is a continuous process, the initial training has the challenge of getting closer to effective teaching practice beyond strictly academic demands.